The acute effect of positive self-talk practices among collegiate badminton athletes in dealing with sports anxiety for sports performance - Abalos, Andrea Y. 2001-
This thesis will be an experimental research design that aims to determine the acute effect of positive self-talk practices among collegiate badminton varsity athletes who compete in the University Athletic Association of the Philippines (UAAP) dealing with sports anxiety for sports performance. Recent research shows that badminton athletes experience sports anxiety both during training periods and competition season (Duncan, et al., 2017). It was also found that coping strategies such as self-talk have demonstrated their efficacy in managing sports-related anxiety-inducing situations (Nadja, Walter ., et al., 2019). This is why this research will look into self-talk as a specific coping strategy and its effect in dealing with sports anxiety on sports performance. The participants will be composed of collegiate badminton varsity members who will follow an inclusion and exclusion criteria. The participants will undergo a short-term self-talk intervention which consists of 3 sessions with a duration of 60 minutes. They will be made to answer 3 questionnaires namely the following: Sport Anxiety Scale-2 (SAS-2), Automatic Self-Talk Questionnaire for Sports (ASTQS), and the Athlete’s Subjective Performance Scale (ASPS) — wherein a dependent t-test will be used to compare the pre-test versus post-test differences among the questionnaire scores. Descriptive statistics will also be used to summarize and describe the questionnaire scores and results.